2013
DOI: 10.1016/j.vhri.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization and the Caregiver Burden of Dementia in China

Abstract: China faces multiple obstacles in preparing to care for its fast-growing dementia population. Better understanding of patients and caregivers may mitigate these challenges by improving awareness and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
3
31
1
Order By: Relevance
“…Time spent caring refers to both hours per day or week spent on caring activities and the period of caregiving since the onset of dementia. Six studies explored the relationship between time spent caring and carer outcomes. The evidence suggests that more hours spent caring per week were associated with higher burden and lower perceived quality of life among family carers .…”
Section: Context Of Caringmentioning
confidence: 99%
See 3 more Smart Citations
“…Time spent caring refers to both hours per day or week spent on caring activities and the period of caregiving since the onset of dementia. Six studies explored the relationship between time spent caring and carer outcomes. The evidence suggests that more hours spent caring per week were associated with higher burden and lower perceived quality of life among family carers .…”
Section: Context Of Caringmentioning
confidence: 99%
“…In contrast, Gaugler and colleagues found that carers who spent more time providing care were more likely to be classified as resilient. Although there were fewer studies exploring the impact of the duration of care on carer outcomes, a longer duration of caregiving was associated with a reduction in tangible support from others and increased carer burden …”
Section: Context Of Caringmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Due to social norms, 75-80% of the responsibility for taking care of the elderly is assumed by women. [7][8][9] It has been suggested that there are several social and cultural demands on women to adopt the role of a caregiver within the family. 6 While caregiving provides a suitable care and supportive environment for older adults, changes in the lives of these caregiving family members also affect their health.…”
Section: Introductionmentioning
confidence: 99%